Optical coherence tomography of the pancreatic and bile ducts: are we ready for prime time? - Tyberg, Amy; Raijman, Isaac; Novikov, Aleksey A.; Sejpal, Divyesh V.; Benias, Petros C.; Trindade, Arvind J.; Das, Ananya; Sachdev, Mankanwal; Khosravi, Farhoud; Tarnasky, Paul; Kedia, Prashant; Gaidhane, Monica; Kahaleh, Michel; Joshi, Virendra (Endoscopy International Open, 2020)
Background and study aims First-generation optical coherence tomography (OCT) has been shown to increase diagnostic sensitivity for malignant biliary and pancreatic-duct strictures. A newer OCT imaging system, NVision Volumetric Laser Endomicroscopy (VLE), allows for in vivo cross-sectional imaging of the ductal wall at the microstructure level during endoscopic retrograde cholangiopancreatography (ERCP). The aim of this study was to identify and evaluate characteristics on OCT that are predictive of benign and malignant strictures.Patients and methods Consecutive patients from six centers who underwent OCT between September 2016 and September 2017 were included in a dedicated registry. OCT images were analyzed, and nine recurring characteristics were further assessed. Final diagnosis was based on histology and/or surgical pathology.Results 86 patients were included (49 % male, mean age 64.7). OCT was performed in the bile duct in 79 patients and the pancreatic duct in seven. Nine OCT characteristics were identified: dilated hypo-reflective structures (n = 7), onion-skin layering (n = 8), intact layering (n = 17), layering effacement (n = 25), scalloping (n = 20), thickened epithelium (n = 42), hyper-glandular mucosa (n = 13), prominent blood vessels (n = 6), and a hyper-reflective surface (n = 20). Presence of hyper-glandular mucosa, hyper-reflective surface and scalloping significantly increased the odds of malignancy diagnosis by 6 times more (P = 0.0203; 95 % CI 1.3 to 26.5), 4.7 times more (P = 0.0255; 95 % CI 1.2 to 18.0) and 7.9 times more (P = 0.0035; 95 % CI 1.97 to 31.8) respectively.Conclusion By providing in-vivo cross-sectional imaging of the pancreatic and biliary duct wall, OCT technology may improve sensitivity in diagnosing malignant strictures and provide standardizable criteria predictive of malignancy.